2019
DOI: 10.3847/1538-4357/ab3977
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Field RR Lyrae as Galactic Probes. I. The Oosterhoff Dichotomy Based on Fundamental Variables*

Abstract: We collected a large data set of field RR Lyrae stars (RRLs) by using catalogues already available in the literature and Gaia DR2. We estimated the iron abundances for a sub-sample of 2,382 fundamental RRLs (∆S method: Ca II K, Hβ, Hγ and Hδ lines) for which are publicly available medium-resolution SDSS-SEGUE spectra. We also included similar estimates available in the literature ending up with the largest and most homogeneous spectroscopic data set ever collected for RRLs (2,903). The metallicity scale was va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 163 publications
(255 reference statements)
3
44
0
Order By: Relevance
“…For the Oo II group the median value of the amplitude of the hump is equal to (12 ± 5) · 10 −2 , and for the Oo I population its value is (10 ± 5) · 10 −2 . The median value for the amplitude o the bump is again similar for both Oo types, (6 ± 1) · 10 −2 (Oo I stars) and (5 ± 2) · 10 −2 (Oo II stars), which is in agreement with the population effect of the Oosterhoff dichotomy as suggested by Fabrizio et al (2019).…”
Section: Shocks In the Color-magnitude Diagramsupporting
confidence: 86%
See 1 more Smart Citation
“…For the Oo II group the median value of the amplitude of the hump is equal to (12 ± 5) · 10 −2 , and for the Oo I population its value is (10 ± 5) · 10 −2 . The median value for the amplitude o the bump is again similar for both Oo types, (6 ± 1) · 10 −2 (Oo I stars) and (5 ± 2) · 10 −2 (Oo II stars), which is in agreement with the population effect of the Oosterhoff dichotomy as suggested by Fabrizio et al (2019).…”
Section: Shocks In the Color-magnitude Diagramsupporting
confidence: 86%
“…Several possible solutions emerged over the past decades, e.g., increased helium abundance for RR Lyrae stars in Oosterhoff typeİI (Oo II) clusters Sandage 1981) or a different direction in crossing the instability strip (van Albada & Baker 1973). In more recent years some progress has been made suggesting that population and/or metallicity effects might be the cause of the Oosterhoff dichotomy, e.g., Catelan (2009); Lee et al (2014); Fabrizio et al (2019), especially among field RR Lyrae variables.…”
Section: Introductionmentioning
confidence: 99%
“…A.1 show that field TIICs cover a broad range in metallicity, from [Fe/H]∼-2 to [Fe/H]∼0.3. The distribution appears to be similar to field RRLs (Magurno et al 2018;Fabrizio et al 2019), suggesting a similar evolutionary channel. Moreover, BLHs, WVs and RVTs appear to have very similar metallicity distributions.…”
Section: Summary and Final Remarksmentioning
confidence: 57%
“…Continuum normalization and Doppler-shift corrections were made using the National Optical Astronomy Observatory libraries for IRAF 2 (Image Reduction and Analysis Facility, Tody 1993). Further information about the sample selection and radial velocity studies for the spectra analysed in this work can be found in Fabrizio et al (2019); Bono et al (2020), andCrestani et al (2021).…”
Section: Spectroscopic Data Setmentioning
confidence: 99%